How multi-component cascades operate in cells: lessons from the ubiquitin system-containing liquid-separated condensates. (3rd September 2021) - Fu, Afu; Livneh, Ido; Ciechanover, Aaron; Cohen-Kaplan, Victoria
ABSTRACT: Membraneless condensates have recently caught the attention of biologists as hubs for cellular components required for catalysis of basic processes. Whether they are real has become the center of heated discussion where the main issues are their mechanism of assembly and function. A recent study describing these condensates as hubs for protein degradation by the ubiquitin system may shed a new light on this recent development in cell biology.